Archaeological evidence of the use of clay as raw material in the argentinian architecture of the early colonial period - Igareta, Ana (Universidad ORT Uruguay, 2019)
The founding of cities in the north and west of the República Argentina during the first century of Iberian conquest was a complex process of trial, error and articulation of a variety of resources and techniques. Raw materials and constructive systems used such cities continue to be one of the great questions of colonial archeology, since the poor conservation of the architectural record limited its analysis and displaced archaeologists interests towards other evidences, more abundant and available.A systematic survey of documents produced by individuals who traveled through the region during the sixteenth century allowed to detect a limited but interesting set of mentions referring to the use of raw clay in the construction of structures, consistent with archaeological finding in the foundational areas of some of those cities. It is expected that this result will contribute to the development of a more detailed characterization of its early architecture, now disappeared.